MOTIVASI DENGAN PRAKTIK PERAWAT DALAM PENCEGAHAN RESIKO JATUH PADA ANAK DI RUMAH SAKIT KABUPATEN KENDAL - Sulastri Sulastri; Budi Wahyudi (LPPM STIKES Muhammadiyah Kendal, 2020)
The risk of falling is susceptible to the patient so that nurse motivation is necessary in preventing the risk of falling child. Nurses are required to prevent falls in patients in care. This study aims to determine the relationship of motivation and practice of nurses and the relationship between motivation and practice of nurses in preventing the risk of falling on the child. This research uses correlation research design with cross sectional design. The sampling technique used total sampling with total sample as much as 108 respondents. The data collection tool uses motivational questionnaire and nursing practice. Data analysis using Sperman Rank test. Data processing is done univariat and bivariat. The results showed good motivation with good nurse practice as much as 47 (43,5%), enough motivation with good nurse practice as much 14 (13%), good motivation with practice nurse is 22 (20,4%), enough motivation with practice nurse while as many as 25 (23.1%). There is a motivational relationship with the practice of nurses in preventing the risk of falling In the Inpatient Room p value 0.01. (<0.05). Suggestions to improve nurse motivation in preventing risk of falling in children so that the risk of falling in children will not happen.